قائمة ملاحظة السمات السلوكية للأطفال الموهوبين ما قبل المدرسة : دراسة استطلاعية - الجغيمان، عبدالله بن محمد; ابو فراش، حسين محمد أحمد (الأكاديمية العربية للتربية الخاصة, 2007)
سعت هذه الدراسة إلى بناء قائمة بالسمات السلوكية الإسهام في الكشف المبكر عن الأطفال الموهوبين في الفئة العمرية 3-6 سنوات. ولتحقيق هذا الهدف تمت مراجعة الأدبيات التي تناولت الكشف عن الموهوبين ضمن هذه الفئة لبناء قائمة بالسمات السلوكية، وتم عرضها على المختصين في المجال لحساب صدق المحكمين. وتم بعد ذلك إجراء دراسة استطلاعية هدفت للتعرف على مدى مناسبة القائمة للبيئة السعودية من حيث وضوح العبارات، ومناسبتها للتعرف على الموهوبين والكشف عنهم في المجتمع السعودي. وقد تم إجراء التحليلات الإحصائية المناسبة التي تمثلت باختبار "ت" للعينة الواحدة، وكذلك تم رصد ردود آراء المعلمات حول وضوح البنود ومناسبتها للكشف عن الموهوبين في هذه الفئة العمرية وبناء على ما سبق من معالجات، تم إخراج القائمة بصورتها النهاية لتستخدم في الكشف المبكر عن الأطفال الموهوبين في الفئة العمرية 3-6سنوات. This study seeks to build up a list of the behavioral characteristics that contributes to an early discovery of gifted children between the ages from 3-6. In order for that goal to be realized, literature that dealt with the mechanisms for spotting the gifted within this age category was reviewed with the aim of establishing a list for their behavioral characteristics. This list had been presented to specialists in that field in order to estimate fidelity of the arbitrators. This done, a pilot study v/as conducted with the aim of recognizing the extent to which the list suits the Saudi environment regarding the clarity of expression and whether it is reliable enough to find out and recognize the gifted in the Saudi environment. Appropriate statistical procedures have been taken in that the "T" specimen for only one species has been examined. Besides, teachers' answers and viewpoints respecting the clarity of items and the extent to which they assist in finding out the gifted within this age category had been recorded. Based on all that is past, the list was made in its final format to be used in the early discovery of the gifted children between the ages of 3-6.
Keywords: معلمو رياض الأطفال -- الطفولة -- الأطفال الموهوبون -- الشخصية -- رعاية الموهوبين -- السلوك